The cosmetic dye quinoline yellow causes DNA damage in vitro - Drumond Chequer, Farah Maria; Venancio, Vinicius de Paula; Souza Prado, Maira Rocha de; Silva e Cunha Junior, Luiz Raimundo Campos da; Lizier, Thiago Mescoloto [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP]; Burbano, Rommel Rodriguez; Pires Bianchi, Maria Lourdes; Greggi Antunes, Lusania Maria (Elsevier B.V., 2015)
Quinoline yellow (QY) is a chinophthalon derivative used in cosmetic compositions for application to the skin, lips, and/or body surface. However, regulatory data about the genotoxicity and/or mutagenicity of this compound are still controversial. Therefore, this work evaluated the genotoxicity of QY using the comet assay and the cytokinesis-block micronucleus cytome assay (CBMN-Cyt) in the metabolically competent cell line HepG2, which closely mimics phase I metabolism. This research also identified the products formed after electrochemical oxidation of the QY dye, which simulates hepatic biotransformation. The primary products generated after the oxidation process were analyzed by High Performance Liquid Chromatography coupled with a Diode Array Detector (HPLC/DAD), which detected the production of 4,4'-diaminodiphenylmethane, 2-methoxy-5-methylaniline and 4,4'-oxydianiline. The results demonstrated that low (from 0.5 to 20 mu g mL(-1)) QY concentrations were genotoxic in HepG2 cells on both assays and those harmful compounds were detected after the oxidation process. Our findings suggest that this colorant could cause harmful effects to humans if it is metabolized or absorbed through the skin. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Genotoxicity; Cosmetic dye; Micronucleus; Comet assay; Oxidation